Leakage after sleeve gastrectomy: Endoscopic stenting VS surgical intervention - Abdelhamid, Mohamed Salah; Gharib, Ahmed Zaki; Mohammed, Mohammed Abdelaal; El Gindy, Tarek Mahmoud Ibraheem (Archives of Surgery and Clinical Research, 2020)
Background: Laparoscopic sleeve gastrectomy (LSG) is becoming more popular in the treatment of obesity. LSG is safe with a low morbidity. The complications rarely result in morbidity and even mortality. Leaks are the major complication associated with LSG with a reported prevalence between 1.9% and 2.4%. Objective: To compare surgical intervention and endoscopic stenting for treatment of gastric leakage after sleeve gastrectomy. Patients and method: Our study included 30 patients presented with post sleeve leaks discovered by routine postoperative imaging or during the follow up period. Patients were recruited from October 6th university hospital during the period from August 2017 to August 2019. Patients were divided to the following groups: 1) Endoscopy group: This included 15 patients with post sleeve leakage undergoing endoscopic stent insertion. 2) Surgery group: which included 15 patients with post sleeve leak age undergoing surgical management. This division was random. Results: Our study showed that Endoscopic stenting for management of post sleeve gastrectomy leakage is an effective method with lower morbidity and shorter post-operative hospital stay than surgical management. Some patients may be good candidates for early surgical intervention in type 1 leakage if managed early before dissemination of leakage and before tissues become friable. Complications of stents include stent migration (26%), stent related ulcer (13%) and stricture (13%). while the surgical intervention carries more complications (DVT, chest infection, wound infection and stricture) and longer postoperative hospital stay. Conclusion: endoscopic management of post-sleeve gastrectomy leakage with stenting is recommended because it successfully manages the leaks and avoids invasive procedures with less risk, with shorter hospital stay and early return of function.